POTENSI APLIKASI GRANULOCYTE-COLONY STIMULATING FACTOR VIA MICROCHIP SUBKUTAN SEBAGAI TERAPI PREVENTIF PADA TRAVELER PASCA INFARK MIOKARDIUM - Sasmita, I Gede Yuhana Dharma (E-Jurnal Medika Udayana; Vol 5 No 4 (2016): E-jurnal medika udayana, 2016)
POTENTIAL APPLICATIONS GRANULOCYTE-COLONY STIMULATING FACTOR VIA SUBCUTANEOUS MICROCHIP ON PREVENTIVE THERAPY AFTER TRAVELER MYOCARDIAL INFARCTION Death incidence among travelers with myocardial infarct (MI) highly reported among travelers experiencing previous reperfusion therapy. Pathological remodeling progresivity post MI have a strong corelation with mortality related with cardiac arythmia and heart failure. Cellular cardiomyoplasty considered as one regenerative therapy which capable in preventing post infarct pathological remodeling by applying the multipotency effect of stem cell. Several studies suggest the use of Mesenchymal Stem Cell (MSC) in the term of celluar cardiomyoplasty which focused on endogenous modulation of stem cells. Regarding to those concern, the emerging effectivity of Granulocyte-Colony Stimulating Factor (G-CSF) in modulates MSC endogenously proved to be relevant. From the travel medicine perspective, G-CSF therapy need several considerations including pre travel condition of a patient after reperfusion therapy, risk factors exposure during travel and medical compliance. Therefore, one strategy named microchip drugs delivery system was suggested as a response for the need of increasing drugs efficacy, stable and continuous transfer, high compliance and self-controlled therapy. This review aimed to explore the G-CSF mechanism as MSC modulator, introducing the construction and the mechanism of subcutaneus microchip to facilitate G-CSF therapy, and provide prospective view of G-CSF therapy via subcutaneus microchip among post MI traveler. G-CSF modulates MSC by performing stimulation for MSC mobilization from bone marrow, homing to the infarct zone and regeneration activity. Inside the construction, microchip as a drugs container passed microfabrication process and package into implant capsule. G-CSF release externally controled by radiofrequency signal that induce the microchip membrane degradation followed by drugs release. Furthermore, regarding to the revealed potentiality, G-CSF therapy expected to perform an evidence based preventive therapy for post MI traveler and increase heart functional capacity to adapt with risk exposure during travel. Overall, deep research strongly required.
Keywords: post MI traveler, cardiomyoplasty, MSC, G-CSF, microchip drugs delivery system